Grammar Originality of Iryna Zhylenko’s Individual Style: the Subject’s Semantic Varieties in the Sentence Structure (Linguostylistic Studies, 2022)
This article highlights grammatical features of Iryna Zhylenko’s individual style. The study seeks to identify the semantic varieties of the subjects dependent on the predicate in the poetic works of the writer.  The subject is defined as a predicate-dependent component of a sentence structure. The paper presents a comparative analysis of valence and dependence phenomenon, and the authors substantiate the expediency of the theory of syntactic dependence for the analysis of the semantic-syntactic structure of a sentence. It has been revealed that the predicates that define the dependent subject have the appropriate semantics. The predicate is differentiated into action, process, state, and quality predicates. Analysis of the semantic expression of predicate-dependent subjects allows for distinguishing 4 semantic groups. In the first group, the subject indicates the nomination of a person or a living being. The second group represents the nominations of the subject related to the environment (creatures/objects). The third group includes the subjects that express the substantive meaning. The fourth group deals with the implicit subject (lexically unexpressed subject of the state) with zero expression.  The study argues that the predicates of action and process in the first and third groups determine the dependent components in the sentences. The second group represents the action, process, state, and quality predicates’ presence in sentences. In the fourth group, the dominant components are omnipresent predicates of the all-encompassing state. Sentences in Iryna Zhylenko’s poetry contain fresh original images, and it explains the unusual combination of predicate and dependent subject. The creative style of the writer is characterized by the use of the subject in both the position before the predicate (pre-position) and after the predicate (post-position).
Keywords: sentence structure; syntactic dependency; valency; predicate